2019
DOI: 10.3390/jcm8060852
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Autonomic Derangement Is Associated with Worse Neurological Outcome in the Very Early Phases of Ischemic Stroke

Abstract: Background: Acute ischemic stroke (AIS) is associated with autonomic dysfunction. We evaluated the prognostic value of heart rate variability (HRV) and the role of stroke localization and reperfusion treatment (RT) on autonomic control. Methods: Patients with AIS and sinus rhythm were enrolled in the emergency department. Autonomic parameters were recorded at the onset and after a potential RT. Neurological deficit was assessed using the National Institute of Health Stroke Scale (NIHSS) at the onset and residu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 37 publications
2
11
0
Order By: Relevance
“…Moreover, the results supported previous studies which found that the PNS and SNS were linked to HF and LF, respectively [ 26 , 27 ]. Additionally, the LF/HF ratio was linked to the balance between SNS and PNS [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the results supported previous studies which found that the PNS and SNS were linked to HF and LF, respectively [ 26 , 27 ]. Additionally, the LF/HF ratio was linked to the balance between SNS and PNS [ 28 ].…”
Section: Discussionsupporting
confidence: 90%
“…Abnormal HRV in the acute phase of stroke has been shown to predict unfavorable outcomes in the first 3 months after the ischemic event [105,106]. These findings were confirmed by our group [107], showing that loss of sympathetic rhythmic oscillation could predict a poorer 3-month outcome, and by autonomic evaluation [108,109]. HRV analysis may also predict acute complications of AIS, such as stroke-in-evolution, i.e., early worsening of neurological conditions [110], infarct expansion [95], infections within the first week [111] or possibly even sudden in-hospital death [86].…”
Section: The Predictive Role Of Hrvsupporting
confidence: 84%
“…In in Supplementary Table S3 association between HRV and AIS or ICH evaluated by non-linear analysis is presented. This has been published by Tobaldini et al (2019a) ; Tobaldini et al (2019b) and Chen et al, 2018 and Sykora et al, 2020 . A novel HRV analysis with the use of symbolic analysis consists of three formulas: the pattern with no variation (0V%, representing the sympathetic modulation), the pattern with two similar variations, and the pattern with two different variations (2LV% and 2UV% as markers of vagal modulation, respectively); this has been published by Tobaldini et al (2019b) .…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, there is no universal recommendation which HRV parameters are best for examining the autonomic nervous system. Although researchers have been traditionally using linear time-domain or frequency-domain parameters ( Sethi et al, 2016 ; Chidambaram et al, 2017 ), more recently, researchers have used non-linear parameters such as approximate entropy, multiscale entropy, detrended fluctuations, and fractal dimensions (FDs) ( Tobaldini et al, 2019a ; Tobaldini et al, 2019b ; He et al, 2019 ) to provide additional or alternative insights into the investigated physiological states. Furthermore, the exact mechanism responsible for poor outcomes in patients with stroke showing reduced HRV remains unclear.…”
Section: Introductionmentioning
confidence: 99%